Pharmacy Decision Support Systems: Enhancing Clinical Decision-Making and Medication Safety - G. , Prasanthi (International Journal of Psychosocial Rehabilitation, 2020)
Pharmacy Decision Support Systems (PDSS) have become integral tools in the field of healthcare, aimed at enhancing clinical decision-making and medication safety. This research paper explores the multifaceted role of PDSS in contemporary pharmacy practice and its impact on patient care. Through a comprehensive literature review and analysis, we delve into the benefits, challenges, and future prospects of these systems. As the complexity of healthcare continues to grow, the need for effective clinical decision-making tools becomes increasingly evident. PDSS offers healthcare practitioners a wealth of information, from drug-drug interactions to dosage recommendations, helping them make informed decisions at the point of care. Such systems not only aid in reducing medication errors but also contribute to better patient outcomes and overall quality of care. However, this paper does not overlook the challenges and limitations associated with the implementation and use of PDSS. Issues such as system integration, user acceptance, and data security are addressed to provide a comprehensive view of the landscape. To illustrate the practical applications of PDSS, we present case studies and examples that highlight successful implementations and showcase how these systems have positively impacted clinical practice. Looking forward, this paper discusses the future directions and trends in the field of pharmacy decision support systems, considering the ever-evolving healthcare environment and the potential influence of technological advancements. In conclusion, PDSS offers significant promise for enhancing clinical decision-making and medication safety in pharmacy practice. This paper underscores the importance of these systems in modern healthcare, emphasizing the need for continued research and innovation to maximize their potential.